Introducing the Learning Scorecard: a tool to improve the student learning experience - Cardoso, E. (2020)
Improving the student learning experience is an essential aspect of teaching. This paper presents the Learning Scorecard (LS), a tool designed to monitor and manage the learning experience of students in a course. The LS has a student view and a faculty (or course coordinator) view. The student view essentially focuses on time management and uses gamification to engage students with the course’s activities. In the faculty view, data is aggregated from the student’s view, enabling the course coordinator to monitor the average progress of students in the different classes of the course he/she is lecturing. The Learning Scorecard has been developed using Business Intelligence and performance management techniques. It includes a Balanced Scorecard and dashboards for the visualization and monitoring of the student learning experience. In this paper the design of the LS will be presented as well as some initial results with an ongoing experiment in a course lectured in different Higher Education programs within the same university.